STRATEGIC HUMAN RESOURCE MANAGEMENT AND ITS DETERMINANT FACTORS IN THE THAI NON-PROFIT SECTOR - Singhapol, Pruksa (Asian Administration and Management Review, 2022)
This study aims to examine the extent to which strategic human resource management (SHRM) has been implemented in Thai nonprofit organizations (NPOs) and therefore investigate the determinants influencing the application of SHRM in the sector. The study draws hypotheses by employing the factors from institutional and organizational levels to investigate the pivotal personnel management approach, namely strategic human resource management in the Thai nonprofit sector. The study targets organization as a unit of analysis and investigation. The research methodology is a mix of qualitative and quantitative approaches in which a survey questionnaire and semi-structured interviews were conducted to obtain adequate information to answer key research questions. Research results suggested that five out of eight determinants exhibited for hypothesis testing have a statistically significant relationship and impact on SHRM applications. These determinants are the dependence on external funds, the leader’s competence, the organization’s culture, size, and the use of technology. Unlike the public or private sector, nonprofit organizations have applied the SHRM concept to actual implementation differently based on the type of organizations: foundations, associations, and unregistered civil society organizations (CSOs). Descriptive data also suggested that nonprofit organizations in Thailand have a unique pattern pertaining to SHRM practice in which employee participation is central to their operations and has been adopted more intensely compared to other SHRM attributes. Finally, quantitative, and qualitative analysis confirmed that among five determinant factors that impact SHRM practices, funds are regarded as a vital factor that supports or hinders the success of nonprofit organizations in Thailand.